2010
DOI: 10.1007/s10823-010-9126-6
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of Abandonment and Quality of Life Among Older Persons in Rural Northeast Thailand

Abstract: The purpose of this study was to determine the extent to which older persons in rural Northeast Thailand felt abandoned by the emigration of their children and the impact this may have on their quality of life. A cross sectional survey, consisting of 113 questions including the 26-item WHOQOL-BREF and the 24-item WHOQOL-OLD was administered to 212 participants. Participants ranged in age from 60 to 107 with a mean age of 71. While only 9% were found to live alone, 20% stated that they felt abandoned to some de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 18 publications
(33 reference statements)
2
19
3
Order By: Relevance
“…In the rural environment, the higher scores in the intimacy facet differ from the findings of an international study in which the highest score among elderly residents of rural areas was in social participation (70.29; SD = 17.92) (19) . The intimacy facet evaluates the ability of an elderly individual to relate to other people (11) .…”
Section: Rev Esc Enfermcontrasting
confidence: 89%
See 1 more Smart Citation
“…In the rural environment, the higher scores in the intimacy facet differ from the findings of an international study in which the highest score among elderly residents of rural areas was in social participation (70.29; SD = 17.92) (19) . The intimacy facet evaluates the ability of an elderly individual to relate to other people (11) .…”
Section: Rev Esc Enfermcontrasting
confidence: 89%
“…In the current study, the lowest mean score in the WHOQOL-BREF was reported in the autonomy facet; however, an Asian study reported that rural elderly residents displayed the lowest score in the death and dying facet (48.03; SD = 35.73) (19) . The lowest mean score in the autonomy facet in both regions indicates losses with respect to the independence of the elderly individuals and an impaired ability of these individuals to make their own decisions (11) .…”
Section: Rev Esc Enfermcontrasting
confidence: 65%
“…A feeling of abandonment undermines a person's self-esteem and quality of life [19]. The feeling of abandonment is a perception of the extent to which a person feels that his or her children have failed to fulfil duties under cultural norms [19].…”
Section: Feeling Abandoned They Did Not Want Me Anymorementioning
confidence: 99%
“…The feeling of abandonment is a perception of the extent to which a person feels that his or her children have failed to fulfil duties under cultural norms [19]. The day care centre was symbolic of abandonment by families.…”
Section: Feeling Abandoned They Did Not Want Me Anymorementioning
confidence: 99%
“…In addition, there are no studies which have comprehensively examined the impact of disability on quality of life (QOL) among this population. A study to assess the impact of feelings of abandonment among older persons (i.e., 60 years and older) in a remote, rural area of Northeast Thailand, found a higher than expected rate of self-reported visual disability (48% of the participants reported having difficulty seeing to the extent that it interfered with their daily life) (Sudnongbua, LaGrow, & Boddy, 2010). Further analysis of these data revealed that those who reported having difficulty seeing had lower QOL scores than those who did not (LaGrow, Sudnongbua, & Boddy, 2011b).…”
Section: Introductionmentioning
confidence: 98%